(3OQGSGJ LOhi GdeTQhYs - (3YHO GdcQje(B, (3jYbhHs ((3YeGf(B:s (3OGQ GSGeI(B,s, 2008)
(3JMXi OQGSGJ LOhi GdeTQhY HCgejI HGdZI dCf Cj eTQhY jYJeO Ydi EJHGY CSGdjH YdejI efXeI, MjK GgJe gPG GdcJGH HOQGSI GdLOhi GdGbJUGOjI h GdCgOGa GdefThOI ef gPG GdeTQhY hechfGJ OQGSGJ LOhi GdeTQhYKe cjajI GNJjGQ GdeTQhY GdefGSH GdebJQf HeUGOQ GacGQg hJMOjOg hGYOGOg hOhQJg hcjajI Yed OQGSGJ GdLOhi(B-(3LhGfH Jbjje GdeTQhY ef GdfGMjI GdeGdjI(B-(3OQGSI GdLOhi GdeGdjI hGdGbJUGOjI ddeTQhY ef efXhQ GdGbJUGO Gdbhej hJNWjW GdGSJKeGQGJ hGdLOhi GdGbJUGOjI ddHMK GdYdej hfXGe GdHfGA hGdJTZjds
(3HjHdjhZQGajG U(B. 238s
Keywords: (3EOGQI GdeTQhYGJs; (3OQGSGJ GdLOhis